Progression of Jackhammer Esophagus to Type II Achalasia - Abdallah, Jason (J Neurogastroenterol Motil, 2016)
It has been suggested that patients with certain motility disorders may progress overtime to develop achalasia. We describe a 66 year-old woman who presented with dysphagia for solids and liquids for a period of 18 months. Her initial workup showed normal endoscopy and non-specific esophageal motility disorder on conventional manometry. Six months later, due to persistence of symptoms, the patient underwent a high resolution esophageal manometry (HREM) demonstrating jackhammer esophagus. The patient was treated with a high dose proton pump inhibitor but without resolution of her symptoms. During the last year, the patient reported repeated episodes of food regurgitation and a significant weight loss. A repeat HREM revealed type II achalasia. Multiple case reports, and only a few prospective studies have demonstrated progression from certain esophageal motility disorders to achalasia. However, this report is the first to describe a case of jackhammer esophagus progressing to type II achalasia.